1936
DOI: 10.1111/j.1469-1809.1936.tb02135.x
|View full text |Cite
|
Sign up to set email alerts
|

The Inheritance of Allergic Disease

Abstract: The articles published by the Annals of Eugenics (1925–1954) have been made available online as an historical archive intended for scholarly use. The work of eugenicists was often pervaded by prejudice against racial, ethnic and disabled groups. The online publication of this material for scholarly research purposes is not an endorsement of those views nor a promotion of eugenics in any way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
23
0

Year Published

1937
1937
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(28 citation statements)
references
References 13 publications
5
23
0
Order By: Relevance
“…Moreover, statistical analysis of the authors' own findings (5) in family studies and data previously published lends additional support to the theory. One finding that remains to be explained is the excess of males over females among those developing allergic disease before puberty.…”
Section: The Inheritance Of Allergic Disease* Alexander S Wiener Presupporting
confidence: 53%
“…Moreover, statistical analysis of the authors' own findings (5) in family studies and data previously published lends additional support to the theory. One finding that remains to be explained is the excess of males over females among those developing allergic disease before puberty.…”
Section: The Inheritance Of Allergic Disease* Alexander S Wiener Presupporting
confidence: 53%
“…V aughan (12) while critically analysing the findings of R atner and his co-workers, has cast serious doubts on the validity of their findings. V aughan firmly believes that heredity plays a part in the development of allergy and supports the theory of partial recessive inheritance put forward by W iener et al (13). The exact mechanism by which genetic factors operate is not fully understood.…”
mentioning
confidence: 75%
“…Subsequently, Cooke and V ander V eer (5), Adkinson (1), Balyeat (2), Bray (4), W iener ct al. (13), Bowen (3), Schwartz (11) and several others have provided evidence to show that heredity plays a part in the development of respiratory allergy in general and asthma in particular.…”
mentioning
confidence: 99%
“…Familial aggregation was probably first recognized by Sennertus in 1650. 43 Subsequent familial aggregation studies have examined the prevalence of a disease among the relatives of affected individuals versus control groups to determine the risk attributable to inheritance. In 1952, Schwartz 44 showed that relatives of probands with asthma had increased risk of developing asthma.…”
Section: Genetic Basis For Asthmamentioning
confidence: 99%